Worker Cooperation and the Ratchet Effect - Carmichael, H. Lorne; MacLeod, W. Bentley (Journal of Labor Economics, 2000)
Workers paid by the piece should be happy to introduce new techniques that increase output, but firms always seem to reduce the piece rate when workers start earning too much money. Workers respond by restricting output and keeping good new ideas to themselves. We show that this outcome is inevitable in a competitive environment. However, there are noncompetitive situations where firms can use piece rates to get cooperation from their workers. These predictions are consistent with case history evidence from the cotton spinning industry in England in the nineteenth century and the Lincoln Electric Company in the United States even today. Copyright 2000 by University of Chicago Press.